2020
DOI: 10.3892/ijo.2020.5038
|View full text |Cite
|
Sign up to set email alerts
|

Cyclovirobuxine D inhibits colorectal cancer tumorigenesis via the CTHRC1‑AKT/ERK‑Snail signaling pathway

Abstract: Cyclovirobuxine D (CVB-D) is an alkaloid, which is mainly derived from Buxus microphylla. It has been reported that CVB-D has positive effects on breast cancer, gastric cancer and other malignant tumors. However, to the best of our knowledge, there are no reports regarding the effects of CVB-D on colorectal cancer (CRC). The purpose of the present study was to determine the anticancer effects of CVB-D and further elucidate its molecular mechanism(s). DLD-1 and LoVo cell lines were selected to evaluate the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…In addition to the targeted regulation of CTHRC1 by miRNAs, it has been demonstrated that cyclovirobuxine-D could inhibit the progression and metastasis of CRC cells due to the targeting of CTHRC1 [137]. Therefore, CTHRC1 may be a potential target in combination with antitumor drugs in the future, which can promote the research progress of tumor-targeted drugs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the targeted regulation of CTHRC1 by miRNAs, it has been demonstrated that cyclovirobuxine-D could inhibit the progression and metastasis of CRC cells due to the targeting of CTHRC1 [137]. Therefore, CTHRC1 may be a potential target in combination with antitumor drugs in the future, which can promote the research progress of tumor-targeted drugs.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of mechanism, several studies have found that CVBD, through the CTHRC1-AKT/ERK-Snail pathway or EGFR-FAK-AKT/ERK1/2-Slug pathway, inhibit cancer tumorigenesis through CVBD inducing mitochondrial apoptosis in cancer cells. Moreover, CVBD causes cancer cell death of autophagy associated with the AKT/mTOR pathway ( 14 17 ). Meanwhile, CVBD could active AKT/ERK signaling pathway in T98G and U251.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies suggest that CVBD has an effect on various cancer cells. For instance, CVBD inhibits colorectal cancer tumorigenesis via the CTHRC1-AKT/ERK-Snail signaling pathway ( 14 ), and exerts anticancer effects by suppressing the EGFR-FAK-AKT/ERK1/2-Slug signaling pathway in human hepatocellular carcinoma ( 15 ). Moreover, CVBD inhibits cell proliferation and induces mitochondria-mediated apoptosis in human gastric cancer cells ( 16 ), and induces autophagy-associated cell death via the Akt/mTOR pathway in MCF-7 human breast cancer cells ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a disease that seriously affects human health, being one of the primary causes of death all over the worldwide (Tang et al, 2011;Gohlke et al, 2016;Jiang et al, 2020). Osteosarcoma is a highly aggressive tumor originating from the long bones, which is the most frequent primary malignant tumor in children and adolescents, with a wide spectrum of morphology (Hogendoorn et al, 2010;Yen et al, 2018;Sadykova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%